Basic Principles Of Reform And Connection In The Field Of Higher And Vocational Education In Uzbekistan - Tolibovna, Rakhmonova Aziza; Musayeva, Sh.A.; Kholmamatov, D.H. (The American Journal of Management and Economics Innovations, 2021)
In recent years, specific measures have been taken to innovate the economic and social spheres of the republic, to provide comprehensive support and increase the efficiency of science and research. The article discusses the introduction of new and advanced pedagogical technologies in the development of the education system of the Republic of Uzbekistan and the importance of several important factors in the effective organization of this process and future prospects.